Project-Based Entrepreneurship Learning for Vocational High School Students in Bekasi City - Dellia Mila Vernia (PT FORMOSA CENDEKIA GLOBAL, 2022)
Entrepreneurial learning requires methods that generate students' intentions and motivation. The project-based practice method is an alternative method that is suitable for SMK students. This research uses descriptive qualitative method. Respondents were 7 students, 2 teachers and 2 principals. Data in the form of primary and secondary data, data taken through interviews and documentation. The data is processed through data collection, data reduction, data analysis and conclusions are drawn. Data is tested by triangulation technique. The research was conducted in 2 vocational schools in the city of Bekasi. The results showed that vocational students were able to make hand and face cleaning liquid products and create desktop and web-based PHP information system software applications. The project-based learning process is able to make students work and try to make a product so that they are expected to become reliable entrepreneurs